Association of thoracic aorta calcium and non cardiac vascular events in cardiac disease-free individuals. (February 2016) - Craiem, Damian; Chironi, Dr Gilles; Casciaro, Mariano E.; Sirieix, Marie-Emmanuelle; Mousseaux, Elie; Simon, Alain
Abstract: Objective: Thoracic aorta calcium (TAC) is measurable on the same computed tomography (CT) scan as coronary artery calcium (CAC) but has still unclear clinical value. We assessed TAC and CAC relations with non-cardiac vascular events history in a cohort of subjects at risk for cardiovascular disease. Methods: We analyzed retrospectively 1000 consecutive subjects having undergone CAC detection by non-contrast multi-slice CT with measurement field longer than usual in order to measure total TAC including aortic arch calcium. We also determined partial TAC restricted to ascending and descending thoracic aorta sites by removing arch calcium from total TAC. Calcium deposits were measured with a custom made software using Agatston score. Results: Compared with the rest of the cohort, the 30 subjects with non-cardiac vascular event history had higher median values [95% CI] of total TAC (282 [28–1809] vs 39 [0–333], p < 0.01) and partial TAC (4 [0–284] vs 0 [0–5], p < 0.01) but no different value of CAC (73 [0–284] vs 16 [0–148]). Odds ratio [95% CI] of having non-cardiac vascular event per 1-SD increase in log-transformed calcium value was significant for total TAC but not for CAC, if total TAC and CAC were entered separately (1.56 [1.12–2.24], p < 0.01 and 1.13 [0.86–1.50], respectively) or together (1.57 [1.10–2.32], p < 0.01 and 0.98 [0.73–1.32], respectively) in the logistic adjusted model. Conclusion: TAC assessment simultaneous with CAC detection provides complementary information on the extra coronary component of cardiovascular risk beyond CAC's coronary risk prediction. Further studies are required to prospectively confirm this result. Highlights: Thoracic aorta and coronary calcium are measurable together by computed tomography. CT-assessed thoracic aorta calcium was measured in 1000 consecutive patients. Thoracic aorta calcium is associated with extra coronary arterial disease. Aortic arch adds little to the other aortic sites for predicting this outcome.